Analysis of Startup Process and Its Optimization for a Two-Stand Reversible Cold Rolling Mill - Guangming Liu; Yugui Li; Qingxue Huang; Xia Yang; Aimin Liu (Advances in Materials Science and Engineering)
Dynamic characteristic analysis of a two-stand reversible cold rolling mill in the startup process was carried out. The delay algorithm of the interstand thickness was proposed. A new method combined with the accelerated secant and the tangent methods was established to solve the simultaneous equations. The thickness and interstand tension transition processes with different static tension establishing processes were analyzed. Both mills were operated under constant rolling force control mode in the above process. The results show that the strip thickness in the rolling gap reduces in the static mill screwdown process. The entry stand runs inversely to establish the static interstand tension. This area becomes an abnormal thickness reduction area of the incoming strip. It results in several abnormal interstand tension increases in the subsequent startup process. The tension increase leads to an impact force on the strip that is the main reason of the strip breakage in the startup process. So the static tension establishing process was optimized, and the interstand tension fluctuation and the strip breakage accidents both reduced significantly. The results are beneficial to the startup process of the two-stand reversible cold rolling mill.